Harmless or dangerous?: the eranos conferences in the 1930s from the perspective of national socialist germany - Morawska, Joanna (Archaeus, 2010)
In a handwritten memorandum from June 1936, to be found in the files of the German Reich Ministry of Science and Education, it was suggested that all German applicants should be disallowed participation in the Eranos conference in the following August. Since the objective of the Eranos movement would be totally alien to the German mind, any per- mission for German scholars to join the convention in Switzerland should be refused. The author of the note continued that "The Eranos movement intends to infiltrate our Christian life in the West with oriental and occult ideas claiming to enhance it that way. I think we had enough to quarrel in the last 1936 years with these influences and should no longer tolerate them."